Clinical utility of the anti-cyclic citrullinated peptide assay in children with juvenile idiopathic arthritis - Żuber, Zbigniew; Piezga, Agata; Sobczyk, Małgorzata; Garlicka, Alicja (Reumatologia/Rheumatology, 2006)
Antibodies against cyclic citrullinated peptide (anti-CCP) are considered to be specific for rheumatoid arthritis (RA). Aim: to correlate serum anti-cyclic citrullinated peptide antibody levels with juvenile idiopathic arthritis (JIA). The study group comprised 51 patients with JIA (16 boys, 35 girls). Diagnoses were made using ILAR criteria from 1997, patients mean age was 10.75 years (from 3 to 17 years old), mean disease duration was 2.5 years (from 3 months to 13.5 years). As a control group, anti-CCP were tested in sera of 21 children with neurological diseases. Anti-CCP were tested by enzyme-linked immunosorbent assay (ELISA) in serum, values above 5 relative units (>5 RU/ml) were regarded as positive. Positive anti-CCP values were found in sera of three girls with seropositive polyarticular JIA (5.88%). Anti-CCP positivity is identified rarely in JIA patients; it cannot be used as a diagnostic test with high specificity. Detection of anti-CCP positivity in a specific group of patients: girls with seropositive polyarticular JIA, allow to separate picture closest to the classical form of RA in adult patients.